2018
DOI: 10.1016/j.scitotenv.2017.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of high rate algal ponds for wastewater treatment and resource recovery

Abstract: The aim of this study was to assess the potential environmental impacts associated with high rate algal ponds (HRAP) systems for wastewater treatment and resource recovery in small communities. To this aim, a Life Cycle Assessment (LCA) was carried out evaluating two alternatives: i) a HRAP system for wastewater treatment where microalgal biomass is valorized for energy recovery (biogas production); ii) a HRAP system for wastewater treatment where microalgal biomass is reused for nutrients recovery (biofertili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(81 citation statements)
references
References 46 publications
(85 reference statements)
3
52
0
Order By: Relevance
“…The carbon footprint in WWTPs can be mitigated by decreasing the energy consumption through on-site energy recovery and improving the efficiency of aeration [83][84][85][86][87][88]; • Life cycle assessment (LCA)-LCA constitutes a standardized procedure which is employed for examining the environmental aspects characterizing wastewater treatment plants. This approach was adopted in a few studies in order to investigate the energy-related issues, including the production of biogas as well as AD [89][90][91]; • Data envelopment analysis (DEA)-DEA is commonly used to evaluate the eco-efficiency, frequently when the available data is limited. The eco-efficiency of a treatment plant is determined by integrating such factors as energy consumption, economic cost, removal of pollutants as well as contribution to the global warming effect [24,[92][93][94][95]; • Plant-wide modeling-the performance of wastewater treatment plant can be predicted using simulation tools and analysis of the data pertaining to energy consumption as well as the influent and effluent quality.…”
Section: "Smart Control" In Wastewater Treatmentmentioning
confidence: 99%
“…The carbon footprint in WWTPs can be mitigated by decreasing the energy consumption through on-site energy recovery and improving the efficiency of aeration [83][84][85][86][87][88]; • Life cycle assessment (LCA)-LCA constitutes a standardized procedure which is employed for examining the environmental aspects characterizing wastewater treatment plants. This approach was adopted in a few studies in order to investigate the energy-related issues, including the production of biogas as well as AD [89][90][91]; • Data envelopment analysis (DEA)-DEA is commonly used to evaluate the eco-efficiency, frequently when the available data is limited. The eco-efficiency of a treatment plant is determined by integrating such factors as energy consumption, economic cost, removal of pollutants as well as contribution to the global warming effect [24,[92][93][94][95]; • Plant-wide modeling-the performance of wastewater treatment plant can be predicted using simulation tools and analysis of the data pertaining to energy consumption as well as the influent and effluent quality.…”
Section: "Smart Control" In Wastewater Treatmentmentioning
confidence: 99%
“…The biomass grown in the ponds is then harvested to obtain a clarified effluent. Harvested biomass can be valorized as an organic fertilizer [ 1 ] or to produce bioenergy, with anaerobic digestion (AD) being the most straightforward technology for this purpose [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Economically, it has already been shown that the production of bioproducts from microalgae grown in wastewater is more profitable than the generation of biogas. 50 …”
Section: Resultsmentioning
confidence: 99%